Synthesis and crystal structure of 3-(2-{3-[2-(2-oxooxazolidin-3-yl)ethoxy]quinoxalin-2-yloxy}ethyl)oxazolidin-2-one - Fatima Ezzahra Aboutofil; Nour El Hoda Mustaphi; Olivier Blacque; Tuncer Hökelek; Ahmed Mazzah; Lhoussaine El Ghayati; Nada Kheira Sebbar (Acta Crystallographica Section E: Crystallographic Communications)
In the title compound, C18H20N4O6, one of the oxazolidine rings adopts a twisted conformation and the other is a shallow envelope. In the crystal, weak C—H...O hydrogen bonds and π–π stacking interactions help to consolidate a three-dimensional architecture. The Hirshfeld surface analysis of the crystal structure indicates that the most important contributions for the crystal packing are from H...H (48.4%) and H...O/O...H (29.1%) contacts.